Strategic leadership practices and students’ aspiration outcomes: what works in Malaysian vocational colleges? - Mohd Ali, Hairuddin; Zulkipli, Inas (IIUM Press, 2017)
The main objective of the study is to examine and confirm the relationship between Malaysian vocational college leaders’ strategic leadership practices, in-service training effectiveness and students’ aspiration outcomes. Survey approach was used for data collection using adapted five-point Likert scale instrument. Sixty five (65) vocational colleges and a total of 500 school leaders throughout Malaysia (208 males and 209 females) participated in the study. Descriptive statistics, and SEM statistical tools were used in data analysis. The study revealed that Malaysian vocational college leaders’ strategic leadership practices has direct and indirect (through a mediator) significant causal effect on students’ aspirations outcomes. The findings suggest that each vocational college leaders should have a unique training plan based on his/her needs. Special emphasis should be focused on inculcating the knowledge and skills of strategic leadership practices among the Malaysian vocational college leaders